Edaphic characteristics of Austrian pine (Pinus nigra Arn.) forests in the Višegrad area - Blagojević, Velibor D.; Knežević, Milan N.; Košanin, Olivera D.; Kapović-Solomun, Marijana B.; Lučić, Radovan J.; Eremija, Saša M. (Archives of Biological Sciences, 2016)
This paper presents the results of soil research in Austrian pine (Pinus nigra Arn.) forest communities in the Višegrad area, carried out to determine the basic soil characteristics and eco-production potential of forest habitats as an important basis and framework for the successful management of these forests on the principles of sustainable development. Austrian pine forests in this region are an important and ecologically valuable community. The complexity of the geological structure and relief dynamics are dominant environmental factors that condition the expressed variability of soils in the study area. Forest communities of Austrian pine are formed on the peridotites and serpentinites, eutric ranker (haplic leptosol), eutric cambisol (haplic cambisols) and pseudogley (haplic planosol), dense granular and marl limestones calcomelanosol (mollic leptosol), rendzina (rendzic leptosol) and calcocambisol (leptic cambisol). The productivity of these soils is highly correlated with depth and texture composition, and the impact of these factors is linked with soil type, climate and other site conditions. In the research area, soil types with low production potential such as rankers, rendzinas, limestone and dolomite calcomelanosol are dominant. Deeper variants of eutric cambisol, pseudogley and calcocambisol can be classified as soils with moderate to high production potential.